Arm Holding PLC : ecosystem advantage - Williamson, Peter J., (SAGE knowledge. Cases., 2016)
This case explores how ARM has nurtured the creation of a business ecosystem comprising a large network of different types of partners to develop competitive advantage in the semiconductor industry between 1990 and 2009 and become a leading global player whose IP lies at the core of 95% of mobile phones produced in the world. The case enables students to compare and contrast this ecosystem strategy with the alternative, vertically integrated business model adopted by Intel.